Pengaruh Model Latihan Filanesia Terhadap Performa Pada Atlet Sepakbola Wanita - Munar, Hendri; Ma'mun, Amung; Komarudin, Komarudin; Sucipto, Sucipto; Yuliawan, Ely (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
Filanesia is a philosophy that will become the foundation and the hallmark or character of the Indonesian football game, both for early-age coaching to professionals. This study aims to determine the filanesia training model affects performance in female soccer athletes. The method used is experimental with a pretest-posttest control group design with a sample of 22 people. The instrument used in this study is The Game Performance Assessment Instrument (GPAI). The study sample was given exercise 3 times per week, 90 minutes per time, and continued training for four weeks. The data analysis test showed that the results of the Paired Samples T Test had a significance value of 0.000 < 0.05 and the Independent Samples T Test test had a significance value of 0.009 < 0.05 with a difference in the average increase, namely the filanesia exercise group = 0.89 and the control group = 0.61. The results show the conclusion of this study that there is a significant effect of the philanthropic training model on improving performance in women's soccer athletes, and the filanesia training model is proven to be practical training for female soccer athletes.